China and Indonesia's responses to maritime disputes in the South China Sea: forming a tacit understanding on security. (March 2023) - Zou, Yizheng
Abstract: While China does have maritime disputes with its neighbors in the South China Sea, it is also assisting the relevant countries in maintaining economic and legitimate security. By creating mutual trust and tacit understanding over security, China is ultimately ensuring a safe and stable surrounding environment. Although Indonesia needs China's investment in the Belt and Road Initiative, the positions of religious organizations, the military, and the president are not always aligned. Nevertheless, the two sides adopt unyielding positions on the Natuna issue while maintaining a high degree of military deterrence and diplomatic representations. Simultaneously, they strictly avoid any military friction and deal with the issues in a restrained manner. In any potential crisis, such a tacit understanding of security may be one of the best outcomes for China and Indonesia in dealing with disputes in the South China Sea.